2009
DOI: 10.1007/s12111-009-9112-7
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Debate over Nationalism Versus Integration: How Cultural Commitments and Assimilation Trajectories Influence Beliefs About Black Power

Abstract: This paper revisits the longstanding ideological debate over black nationalism versus inter-racial integration. Survey research in this area concentrates on various concerns related to black nationalism. Consequently, scholars know very little about the relative effects of factors influencing the broader variation in beliefs about Black Power. The present study addresses this gap in the literature in several ways, most notably by testing predictions deriving from the Investment in Blackness Hypothesis. This ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…This finding-that an elevated class position encourages attitudinal intricacies and inconsistencies in Black political and social thought-is common to the existing literature (Anderson, 1999;Dawson, 2001;Lacy, 2007;Patillo, 2003;Pew, 2007;Shelton & Emerson, 2010;Shelton & Wilson, 2009). Blacks in the second highest (OR = 0.88) and highest (OR = 0.83) income categories are more likely to declare the equality of opportunity in America, whereas those with at least some college (OR = 1.28), a college degree (OR = 1.31), and/or a graduate degree (OR = 1.32) are less likely to do so.…”
Section: The Race and Class Determinants Of Beliefs About Inequalitysupporting
confidence: 65%
See 2 more Smart Citations
“…This finding-that an elevated class position encourages attitudinal intricacies and inconsistencies in Black political and social thought-is common to the existing literature (Anderson, 1999;Dawson, 2001;Lacy, 2007;Patillo, 2003;Pew, 2007;Shelton & Emerson, 2010;Shelton & Wilson, 2009). Blacks in the second highest (OR = 0.88) and highest (OR = 0.83) income categories are more likely to declare the equality of opportunity in America, whereas those with at least some college (OR = 1.28), a college degree (OR = 1.31), and/or a graduate degree (OR = 1.32) are less likely to do so.…”
Section: The Race and Class Determinants Of Beliefs About Inequalitysupporting
confidence: 65%
“…For several decades now, both nationally representative and local area studies have shown that most Americans attribute poverty to individual-level factors. This idea, which is known as structuralism, posits that the American social "system"-or the way that our society's institutions, patterns of relationships, and dynamics of status are organized-constrains opportunities for some people while simultaneously enhancing them for others (Emerson & Smith, 2000;Feagin, 1975;Huber & Form, 1973;Hunt, 1996Hunt, , 2007Shelton & Emerson, 2010;Smith, 1985;Robinson, 2009). 2 However, many Americans believe that factors beyond a person's control strongly influence his or her prospects for success.…”
Section: Individualism Structuralism and Explanations For Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…My coding scheme for these predictors is pivotal: income and education are examined as a series of dummy variables so as to isolate socioeconomic effects for respondents positioned at some of the highest levels of the American class structure. I did not develop a composite measure for socioeconomic status or examine income and education as continuous variables because studies have shown that these approaches can conceal the class-based nuances of higher status Blacks' beliefs (Shelton and Emerson, 2010;Shelton and Wilson, 2009). Regarding income, I established cutoff points on the REALINC variable based on poverty level and median household income data to capture the distribution of respondents with incomes in the "lowest category," "second lowest category," "middle category," "second highest category," and "highest category."…”
Section: Methodsmentioning
confidence: 99%
“…It seems less likely, for example, that Blacks who were socialized in affluent and politically conservative households will feel strongly connected to the majority of Black America, which does not share their economic and political backgrounds (see McClerking 2001, Chap. 2;Shelton and Emerson 2009). It is also possible that some Blacks will reject linked fate because they subscribe to the more individualistic belief that they alone are the masters of their destiny (McClain et al 2009).…”
Section: The Disillusionment Hypothesismentioning
confidence: 99%